Misidentification as Pseudomonas aeruginosa in hospital water supply samples. (March 2023) - Taudien, S.; Leszczynski, W.; Mayer, T.; Loderstädt, U.; Bader, O.; Kaase, M.; Scheithauer, S.
Summary: Drinking water in hospitals is often tested for Pseudomonas aeruginosa because of its virulence potential. This article describes a case where, based on EN ISO 16266, seven of 11 (64%) samples taken simultaneously from the drinking water system at a single hospital tested positive for P. aeruginosa . This resulted in extensive investigations and interventions, and a number of measures were implemented. However, supplementary analyses with more discriminatory power (matrix-assisted laser desorption/ionization time-of-flight mass spectrometry, 16S-rRNA sequencing) ruled out P. aeruginosa completely. The authors wish to raise awareness of this problem, and suggest that diagnostic uncertainty of results obtained by EN ISO 16266 should be indicated on laboratory reports. Wrongly assuming the presence of P. aeruginosa in hospital water supply systems can lead to unnecessary control measures, as analytical uncertainty massively influences the health risk assessment and the remediation measures initiated in medical environments.